Pengaruh Influencer dan Ulasan Pengguna Terhadap Keputusan Pembelian KOnsumen Pada Brand Skincare Avoskin di Media Sosial - Nabila Huria Salsabila; Sri Utami , Kristiana (Universitas 17 Agustus 1945 Semarang, 2024)
This research focuses on the influence of influencers and customer reviews on Avoskin skincare purchases on social media, especially in digital marketing. The goal is to understand their role in consumer behavior, and explore effective marketing strategies to increase sales and loyalty. It aims to provide insight into the importance of influencers and customer reviews in Avoskin's digital marketing success. The research focused on Avoskin Skincare users, by collecting field data through questionnaires to 107 respondents who met the criteria. A quantitative descriptive approach was used to analyze the influence of beauty influencers on purchasing decisions. An online survey was used to explore respondents' opinions about influencers, interest in products, reviews, and purchase factors. Data analysis was conducted descriptively with a table of survey results.This study tested three hypotheses about the influence of influencers and user reviews on purchasing decisions. The first and second hypotheses are supported by previous research, showing the significant influence of influencers and user reviews. The results of the third hypothesis show that both jointly influence purchasing decisions with strong statistical significance. This confirms the important role of influencers and user reviews in shaping consumer purchasing decisions. The results of the study using IBM SPSS 29 confirmed that influencers and customer reviews have a positive and significant impact on purchasing decisions, encouraging consumers to purchase Avoskin skincare products in accordance with the hypothesis. However, this study has limitations in population and references, and only considers three variables. It is recommended that similar studies expand the population and consider additional variables for a more comprehensive analysis.